MAKNA DAN SIMBOL KESENIAN SINTREN SEBAGAI MEDIA DAKWAH ISLAM - Irmawati Irmawati (LPPM STAIS Dharma Indramayu, 2020)
Abstract This research is entitled Meaning and Symbol of Sintren Art as Islamic Da'wah Media. The study aimed to describe the symbols and meaning of Islamic da'wah media in sintren art. It employed a descriptive analysis method with a qualitative approach. The findings of the research revealed that the art of sintren as a medium of Islamic da'wah, from each scene has Islamic symbols and meanings which is a spectacle that guides the public. The Sintren performance has local wisdom values and icons for the people of Cirebon, for example, religious, social, educational, and language values. The results of this research are expected to have the power to foster public appreciation of traditional arts and to socialize the concept of local wisdom values through academic and community education. Keywords: Meaning, Sintren Art Symbols, Dakwah media